2014
DOI: 10.1002/ijc.28868
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of HIF1α and HIF2α on chromaffin cell phenotypic features and tumor cell proliferation: Insights from MYC‐associated factor X

Abstract: Pheochromocytomas and paragangliomas (PPGLs) are catecholamine-producing chromaffin cell tumors with diverse phenotypic features reflecting mutations in numerous genes, including MYC-associated factor X (MAX). To explore whether phenotypic differences among PPGLs reflect a MAX-mediated mechanism and opposing influences of hypoxia-inducible factor (HIF)s HIF2a and HIF1a, we combined observational investigations in PPGLs and gene-manipulation studies in two pheochromocytoma cell lines. Among PPGLs from 140 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 50 publications
(108 reference statements)
7
75
0
Order By: Relevance
“…Our results verified PNMT hypermethylation previously reported in SDHBrelated PPGLs (2). PNMT hypomethylation in RET-and NF1-and hemimethylation in VHL-related PPGLs is highly consistent their associated neurochemical phenotypes (2,20,29). However, this model does not explain why other "cluster 1" tumors do not display an adrenergic phenotype, even when PNMT is hemimethylated.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results verified PNMT hypermethylation previously reported in SDHBrelated PPGLs (2). PNMT hypomethylation in RET-and NF1-and hemimethylation in VHL-related PPGLs is highly consistent their associated neurochemical phenotypes (2,20,29). However, this model does not explain why other "cluster 1" tumors do not display an adrenergic phenotype, even when PNMT is hemimethylated.…”
Section: Discussionsupporting
confidence: 90%
“…Also, this does not explain why MAX-associated tumors, showing PNMT hypomethylation comparable to RET and NF1 tumors, do not display a predominantly adrenergic phenotype. In this context, Qin and colleagues (2014) provided evidence that addressed these paradoxes in other "cluster 1" tumors characterized by both EPAS1 expression and stabilization of HIF protein (20). In that study, the authors showed that EPAS1 completely blocked effects of steroid-induced PNMT expression in PC12 cells (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, it reduced the ratio of epinephrine to norepinephrine and increased the percentage of dopamine relative to total catecholamines. High dopamine levels in adrenomedullary tumors associate with a more aggressive phenotype, suggesting the presence of immature cancer cells [23][24][25]. On the other hand, the increase in relative dopamine content can be interpreted as a result of enhanced differentiation/ maturation of dopamine-producing TH+ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of HIF-2α is relatively common in VHL deficiency-related pheochromocytoma, whereas HIF-1α is more frequent in succinate dehydrogenase-deficient pheochromocytoma (Pollard et al 2006). Interestingly, it was reported that HIF-1α and HIF-2α exert opposite effect in pheochromocytoma, suggesting the signaling pathways may be similar but the downstream effects are divergent (Qin et al 2014). The distinct effects of HIF-1α and HIF-2α were also observed in adrenal neuroblastoma.…”
Section: Adrenal Cancermentioning
confidence: 98%